Does Bilateral Trust Affect International Movement of Goods and Labor - Eva Spring; Volker Grossmann (Center for Economic Studies and ifo Institute (CESifo), 2013)
Trust in the citizens of a potential partner country may affect the decision to trade with or to migrate to a foreign country. This paper employs panel data to examine the causal impact of such bilateral trust on international trade and migration patterns. We apply instrumental variables (IV) approaches that capture the exogenous variance of bilateral trust separately with eight indicators of genetic ('somatic') distance between country-pairs. These indicators work equally well at the first stage. However, second-stage results very much depend on the exact measure employed as instrument. Overall, we find little evidence that bilateral trust affects international movements of goods and labor. More generally, we highlight the potential fragility of IV estimations even when the instruments seem plausible on theoretical grounds and when standard statistical tests confirm their validity.
Keywords: F10; F22; Z10; 330; bilateral trust; international migration; international trade; instrumental variables; somatic distance